The Hidden Lives of Congregations: Discerning Church Dynamics - Galindo, Israel (Rowman & Littlefield Publishers, 2004)
Faced with crisis, lack of direction, or just plain "stuckness," many congregations and their leaders are content to deal only with surface issues and symptoms—only to discover that the same problems keep recurring, often in different, and more serious, ways. In The Hidden Lives of Congregations, Christian educator and consultant Israel Galindo takes leaders below the surface of congregational life to provide a comprehensive, holistic look at the corporate nature of church relationships and the invisible dynamics at play. Informed by family systems theory and grounded in a wide-ranging ecclesiological understanding, Galindo unpacks clearly the factors of congregational lifespan, size, spirituality, and identity and shows how these work together to form the congregation’s hidden life. He provides useful tools for diagnosing and understanding how one’s congregation fits into the various categories he names and suggests what leadership skills are necessary to get beyond the impasse of surface issues and help the congregation achieve its mission. The Hidden Lives of Congregations provides one of the most far-reaching looks into the invisible nature of faith communities written in recent years. For seminaries and divinity schools, it provides a standard text for getting a solid start in congregational practices; for experienced pastors, it provides support for renewing ministry; for lay leaders and committees, it offers insight to deepening mutual ministry. Israel Galindo has written an indispensable manual that leaders will return to repeatedly for new wisdom and guidance